Peningkatan Hasil Produksi, Penguatan Pemasaran Pada UKM Mak “Plengeh” Kediri - Sri Andayani; Nekky Rahmiyati; Endang Indartuti (Forum Kerjasama Pendidikan Tinggi, 2021)
The impact of the Covid 19 virus has a profound effect on the national economy, including the presence of MSMEs. One of the smes affected in east Java is ukm